Magnet-Bead Based MicroRNA Delivery System to Modify CD133+ Stem Cells - Paula Müller; Natalia Voronina; Frauke Hausburg; Cornelia A. Lux; Frank Wiekhorst; Gustav Steinhoff; Robert David (Hindawi Limited, 2016)
Aim. CD133+ stem cells bear huge potential for regenerative medicine. However, low retention in the injured tissue and massive cell death reduce beneficial effects. In order to address these issues, we intended to develop a nonviral system for appropriate cell engineering. Materials and Methods. Modification of human CD133+ stem cells with magnetic polyplexes carrying microRNA was studied in terms of efficiency, safety, and targeting potential. Results. High microRNA uptake rates (~80-90%) were achieved without affecting CD133+ stem cell properties. Modified cells can be magnetically guided. Conclusion. We developed a safe and efficient protocol for CD133+ stem cell modification. Our work may become a basis to improve stem cell therapeutical effects as well as their monitoring with magnetic resonance imaging.